Determination of Climatic Type of the Kuhdasht Synoptic Meteorological Station of Lorestan Province, Iran - Adinehvand, Mojtaba (National Geographical Journal of India, 2022)
The climatic behavior of each area is predictable using the long-term data and applying the appropriate method of climatic classification for the area under study. The basic objective of the present study is to determine the climatic type of the Kuhdasht synoptic meteorological station and to achieve the desirable result , the following steps have been followed. At the first stage, we collected the total annual rainfall and average annual temperature data for the Kuhdasht meteorological station from year 1998 up to year 2014 for the duration of 17 years. At the second step using the De Martonne method drought coefficient for each listed years has been calculated. At last ,drought coefficient obtained for 17 years is being averaged which comes to 14.40. As per De Martonne classification table, climatic type of the Kuhdasht synoptic meteorological station falls into the category of Semi-dry climate. This means that the Kuhdasht station experiences a dry season followed by rainy season. The dry season would be at least, more than three months. In the case of Kuhdasht station, it observes dry season or low rainfall season for longer period than its rainy season and often observes the activities associated with an air mass in range of our study station during every year